Early Detection of Right Ventricular Dysfunction by Myocardial Performance Index in Diabetic Patients - Nahar, Samsun; Ahmed, Choudhury Meshkat; Siddique, Md Abu; Parveen, Tanjima; Shakil, Shiblee Sadeque; Hoque, Md Harisul (University Heart Journal, 2015)
In diabetes mellitus (DM) patients, left ventricular dysfunction is widely evaluated and established by conventional diagnostic methods, whereas right ventricular (RV) function is not sufficiently evaluated. The aim of this study was to assess the right ventricular function in type 2 diabetic patients by myocardial performance index (MPI) . In this cross-sectional study, 49 diabetic patients and 49 non-diabetic healthy volunteers were studied who were devoid of any other conditions that may influence the both systolic and diastolic function of the RV. In addition to 2D and M-mode evaluation, standard Doppler, pulsed tissue Doppler of both ventricles were performed. MPI was significantly (p<0.05) higher in diabetic patients compared to control group . Right ventricular early diastolic velocity (E) and late diastolic velocity (A), E/A were significantly (p<0.05) lower in DM compared to control group. Myocardial performance index is a useful noninvasive tool for the detection of early right ventricular systolic and diastolic dysfunction in diabetic patients . University Heart Journal Vol. 10, No. 1, January 2014; 3-6